Climate-surface-pore-water interactions on a salt crusted playa: implications for crust pattern and surface roughness development measured using terrestrial laser scanning - Nield, J; Wiggs, G; King, J; Bryant, R; Eckardt, F; Thomas, D; Washington, R (Wiley, 2015)
Sodium accumulating playas (also termed sodic or natric playas) are typically covered by polygonal crusts with different pattern characteristics, but little is known about the short‐term (hours) dynamics of these patterns or how pore water may respond to or drive changing salt crust patterning and surface roughness. It is important to understand these interactions because playa‐crust surface pore‐water and roughness both influence wind erosion and dust emission through controlling erodibility and erosivity. Here we present the first high resolution (10−3 m; hours) co‐located measurements of changing moisture and salt crust topography using terrestrial laser scanning (TLS) and infra‐red imagery for Sua Pan, Botswana. Maximum nocturnal moisture pattern change was found on the crests of ridged surfaces during periods of low temperature and high relative humidity. These peaks experienced non‐elastic expansion overnight, of up to 30 mm and up to an average of 1.5 mm/night during the 39 day measurement period. Continuous crusts however showed little nocturnal change in moisture or elevation. The dynamic nature of salt crusts and the complex feedback patterns identified emphasize how processes both above and below the surface may govern the response of playa surfaces to microclimate diurnal cycles.